Self-publishing and collection development : opportunities and ch allenges for libraries - Holley, Robert P. (West Lafayette, Indiana : Purdue University Press, 2015)
"The current publishing environment has experienced a drastic change in the way content is created, delivered, and acquired, particularly f or libraries. With the increasing importance of digital publishing, mor e than half the titles published in the United States are self-publishe d. With this growth in self-published materials, librarians, publishers , and vendors have been forced to rethink channels of production, distr ibution, and access as it applies to the new content. Self-Publishing a nd Collection Development: Opportunities and Challenges for Libraries w ill address multiple aspects of how public and academic libraries can d eal with the increase in self-published titles"--
Editor's introduction / Robert P. Holley, Wayne State University -- E-book self-publishing and the Los Gatos Library: a case study / Henry Bankhead, Los Gatos Library -- Supporting self-publishing and local aut hors: from challenge to opportunity / Melissa DeWild and Morgan Jarema, Kent District Library -- Do large academic libraries purchase self-pub lished books to add to their collections? / Kay Ann Cassell, Department of Library and Information Science, Rutgers University -- Why academic libraries should consider acquiring self-published books / Robert P. H olley, Wayne State University -- Digital authoring, electronic scholars hip, and libraries: from walled garden to wilderness / Donald Beagle, B elmont Abbey College, Abbot Vincent Taylor Library -- Book vendors and self-publishing / Bob Nardini, Vice President, Library Services, Proque st Books -- Ingram and independent publishing / Robin Cutler, Independe nt Publishing, Ingram Content Group -- Review sources of interest to li brarians for independently published books / Eleanor I. Cook, East Caro lina University -- Self-publishing and bibliographic control / Robert P . Holley, Wayne State University -- Self-publishing and libraries: the slush pile is the platform / Tom Bruno, Yale University Library, Yale U niversity -- An indie author in a library world / Altonya Washington, A ndrew Carnegie Library, Livingstone College -- The romance of self-publ ishing / Elizabeth Nelson, McHenry County College -- Alacrity House Pub lishing LLC / Frankie l. Colton, Alacrity House Publishing LLC -- Self- publishing: a bibliographic essay / Joseph D. Grobelny, College Hill Li brary, Front Range Community College.
Includes bibliographical references and index.
Keywords: Acquisition of privately printed books; Collection development (Libraries); Libraries and publishing; Self-publishing.